Synthesis and Antitumor Activities of Some New N1‐(Flavon‐6‐yl)amidrazone Derivatives. Issue 6 (24th February 2014) - Habashneh, Almeqdad Y.; El‐Abadelah, Mustafa M.; Zihlif, Malek A.; Imraish, Amer; Taha, Mutasem O.
<x xml:space="preserve">Abstract</x> A new series of N1‐(flavon‐6‐yl)amidrazones were synthesized by reacting the hydrazonoyl chloride derived from 6‐aminoflavone with the appropriate sec‐cyclic amines. The antitumor activities of these compounds were evaluated on breast cancer (MCF‐7) and leukemic (K562) cell lines. Among the compounds tested, the N‐morpholine derivative was the most active against the MCF‐7 and K562 cell lines, with IC50 values of 5.18 and 2.89 μM, respectively. Our docking studies showed that the N‐morpholino derivative fits and blocks the oncogenic tyrosine kinases bcr/abl and epidermal growth factor receptor (EGFR) in a similar fashion to that of the potent anticancer agent imatinib.